Diurnal cycling of sea surface temperature, salinity, and current in the CESM coupled climate model. Issue 5 (27th May 2015) - Large, W. G.; Caron, J. M.
Abstract A simple scheme is developed to represent Sea Surface Diurnal Cycling (SSDC) in Coupled General Circulation Models (CGCM). It follows Zeng and Beljaars [2005], but in addition to a night‐time deep well‐mixed ocean boundary layer and a deep day‐time stable layer, a shallow sub‐grid‐scale stable diurnal boundary layer is allowed to develop during the day, followed by a deepening convective layer. These four regimes have empirical property profiles and their governing parameters are determined by comparison of idealized experiments with published in situ and satellite observations. Mixing across the base of the shallow stable layer is governed by a gradient Richardson number, so prognostic equations are solved for salinity and current, as well as temperature. A conclusion is that the timing of peak warming depends on diurnal shear. The SSDC is implemented in the Community Earth System Model (CESM) for multiple purposes: the maximum diurnal amplitude of warming is found to exceed 5°C and to be more than 2°C over most of the ocean; the global distribution of average day‐time minus night‐time SST is used to validate the SSDC against a satellite SST product; and the mean seasonal surface heat flux and precipitation from an uncoupled CESM atmosphere are used to show the climate impacts that might be expected in a CGCM. Two major conclusions are that these impacts are not negligible and that much of the observed signals of diurnal cycling are captured by SSDC without the computational expense of resolving the relevant ocean processes.